Why were they fighting? Why were they dying? The Sacred Defence in Contemporary Young Adult Persian Literature - Szustakiewicz, Piotr (Rocznik Orientalistyczny/Yearbook of Oriental Studies, 2026)
The author of this paper focuses on Persian young adult literature devoted to the Iraq-Iran War, called in Iran Defa’-e Moqaddas (the Sacred Defence). The basis of this paper are six works: one long story and five graphic novels. Based on them, the author analyses what motivations characterize the presented characters, which is the main goal of this paper. It presents values that are worth defending for the presented characters and for which they are ready to sacrifice their lives. He distinguishes three sources of soldiers’ readiness to fight – religiousness, patriotism and personal issues. As based on the characters’ motivation, the author presents the relations between contemporary published texts, the reality of wartime and government’s activities. He examines how they fit into the discourse about the war, which prevails in modern-time Iran and what makes them different. Author also tries to relate them to Iran’s history and Persian culture with the aim to frame analysed texts and motivations in larger context.